EFFECT OF DIFFERENT LEVEL OF ORGANIC AND COMPOUND FERTILIZERS ON FRUIT YIELD APPLE CV.ANNA.(Malus domestica ) - AL-Hamadani, Khalid A.; AL-Muhamide, Omar H.; Mahmood, Ahmed H. (Diyala Agricultural Sciences Journal, 2011)
This studuy was carried out during the growing season 2009 – 2010 on apple cv Anna in vineyard at Radwania region (35 km – western Baghdad). Trees were planting accordining asquare methods. The aimes of this study were at investigat the effect of different level organic and compound fertilizer (0, 5, 10, 15 kg/tree) for the former and (0, 100, 200, 300g fertilizers and quality characteristics on vegetative growth .Randomized complete Block Design (RCBD) was used (tree replicates for each treatment combination). The result obtaind revealed that the treatment (15 kg/tree) organic fertilizers plant was superior significantly in fruit Yield (86.33 kg ree) and other quality characteristics as compared with other treatment, as compaired with the control treatment (75.58 kg ree). The compound fertilizer treatment plants of (300 g ree) gave the higher Yield (95.29 kg ree) and higher quality values as compared with other treatment plants, similarly a lower fruit Yield (58.00 kg ree). A significant interaction effect were recorded between the two fertilizer used regarding fruit Yield and other quality traits. 15 kg ree and the 300 g ree compound fertilizer gave the highest fruit Yield (110.00 kg ree), whereas control treatment gave the lowest Yield (48.33 kg ree). It can be suggested that an organic fertilizer level of 15 kg ree and compound fertilizer level of 300 g ree may be used effectively for higher fruit Yield and quality characteristics apple cv Anna.